Combined small molecule and loss-of-function screen uncovers estrogen receptor alpha and CAD as host factors for HDV infection and antiviral targets. Issue 1 (4th March 2019) - Verrier, Eloi R; Weiss, Amélie; Bach, Charlotte; Heydmann, Laura; Turon-Lagot, Vincent; Kopp, Arnaud; El Saghire, Houssein; Crouchet, Emilie; Pessaux, Patrick; Garcia, Thomas; Pale, Patrick; Zeisel, Mirjam B; et al.
Abstract : Objective: Hepatitis D virus (HDV) is a circular RNA virus coinfecting hepatocytes with hepatitis B virus. Chronic hepatitis D results in severe liver disease and an increased risk of liver cancer. Efficient therapeutic approaches against HDV are absent. Design: Here, we combined an RNAi loss-of-function and small molecule screen to uncover host-dependency factors for HDV infection. Results: Functional screening unravelled the hypoxia-inducible factor (HIF)-signalling and insulin-resistance pathways, RNA polymerase II, glycosaminoglycan biosynthesis and the pyrimidine metabolism as virus-hepatocyte dependency networks. Validation studies in primary human hepatocytes identified the carbamoyl-phosphatesynthetase 2, aspartate transcarbamylase and dihydroorotase (CAD) enzyme and estrogen receptor alpha (encoded by ESR1 ) as key host factors for HDV life cycle. Mechanistic studies revealed that the two host factors are required for viral replication. Inhibition studies using N-(phosphonoacetyl)-L-aspartic acid and fulvestrant, specific CAD and ESR1 inhibitors, respectively, uncovered their impact as antiviral targets. Conclusion: The discovery of HDV host-dependency factors elucidates the pathogenesis of viral disease biology and opens therapeutic strategies for HDV cure.